Wine and Myrrh as Medicaments or a Commentary on Some Aspects of Ancient and Byzantine Mediterranean Society - Rzeźnicka, Zofia; Kokoszko, Maciej (Studia Ceranea, 2019)
The present study has resulted from a close reading of prescriptions for therapeutic wines inserted in book V of De materia medica by Pedanius Dioscorides, the eminent expert in materia medica of the 1st century A.D. The authors emphasise the role of wine varieties and selected flavourings (and especially of myrrh) in order to determine the social status of those to whom the formulas were addressed. This perspective gives the researchers ample opportunity for elaborating not only on the significance of wine in medical procedures but also for underscoring the importance of a number of aromatics in pharmacopoeia of antiquity and Byzantium. The analysis of seven selected formulas turns out to provide a fairly in-depth insight into Mediterranean society over a prolonged period of time, and leads the authors to draw the following conclusions. First, they suggest that medical doctors were social-inequality-conscious and that Dioscorides and his followers felt the obligation to treat both the poor and the rich. Second, they prove physicians’ expertise in materia medica, exemplifying how they were capable of adjusting market value of components used in their prescriptions to financial capacities of the patients. Third, the researchers circumstantiate the place of medical knowledge in ancient, and later on in Byzantine society. Last but not least, they demonstrate that medical treatises are an important source of knowledge, and therefore should be more often made use of by historians dealing with economic and social history of antiquity and Byzantium.